Acoustic Float for Marine Mammal Monitoring - Jones, Christopher; Matsumoto, Haru; Mellinger, David K.; Dziak, Robert P. (2010)
Our goal is to develop an inexpensive acoustic profiler technology, QUEphone (Quasi-Eulerian phone), which allows accurate detection of the beaked whales and reporting in a short time frame by monitoring for the vocalizations of the target species. By converting a commercially available profiler float to a mobile platform and installing a sophisticated detection algorithm on a high-power DSP, and testing the QUEphones in appropriate beaked whale habitat, we were able to compare beaked whale detection results against the Navy's well-established acoustic surveillance system and verify the correct operation of the system. Future work entails making QUEphones easy to operate so that an area can be monitored in advance of an operation by number of these relatively inexpensive instruments for the presence of beaked whales or other species of concern. The original document contains color images. Prepared in collaboration with the Cooperative Institute for Marine Resource Studies at Oregon State University, Newport, OR.